Stock market reaction to financial statement certification by bank holding company CEOs - Beverly Hirtle (Federal Reserve Bank of New York, 2003)
In 2002, the Securities and Exchange Commission mandated that the chief executive officers of large, publicly traded firms certify the accuracy of their company financial statements. In this paper, I investigate whether CEO certification has had a measurable effect on the stock market valuation of the forty-two bank holding companies subject to the SEC order. I find that these firms experienced a positive average abnormal return of 30 to 60 basis points on the day of certification - a result driven primarily by those BHCs that certified ahead of the SEC's deadline. Characteristics associated with greater opaqueness - BHC asset size, liquid asset holdings, and the extent of risky and information-intensive lending-are systematically associated with these certification day abnormal returns. In addition, average returns for not-yet-certifying BHCs were positive, though not statistically significant, on the first two certified, lending weak support to idea that early by some may have signaled investors other likely certify. Overall, results suggest requirement provided relevant information was thus an effective public policy tool, at least banking sector.
Keywords: G21; G28; G38; 330; Aktienmarkt; Ankündigungseffekt; Jahresabschluss; Führungskräfte; Bank; Holding; USA